Nonspecific Symptoms Lack Diagnostic Accuracy for Infection in Older Emergency Department Patients - Caterino, Jeffrey M. (J Am Geriatr Soc, 2018)
OBJECTIVES: To determine if nonspecific symptoms and fever affect the posttest probability of acute bacterial infection in older emergency department (ED) patients. DESIGN: Preplanned, secondary analysis of a prospective observational study SETTING: Tertiary care, academic ED. PARTICIPANTS: 424 ED patients ≥65 years old, including all chief complaints. MEASUREMENTS: We identified presence of altered mental status, malaise/lethargy, and fever as reported by the patient, as documented in the chart, or both. Bacterial infection was adjudicated by agreement among ≥2 of three expert reviewers. Odds ratios were calculated using univariable logistic regression. Positive and negative likelihood ratios (PLR, NLR) were used to determine each symptom’s effect on posttest probability of infection. RESULTS: Of 424 subjects, 77 (18%) had bacterial infection. Accounting for different reporting methods, presence of altered mental status (PLR range 1.40–2.53) or malaise/lethargy (PLR range 1.25–1.34) only slightly increased posttest probability of infection. Their absence did not assist with ruling out infection (NLR >0.50 for both). Fever ≥38°C either before or during the ED visit had moderate to large increases in probability of infection (PLR 5.15–18.10) with initial fever in the ED perfectly predictive, but absence of fever did not rule out infection (NLR 0.79–0.92). Results were similar when analyzing lower respiratory, gastrointestinal, and urinary tract infections individually. 47% of older adults diagnosed with UTI did not complain of UTI symptoms. CONCLUSIONS: The presence of either altered mental status or malaise/lethargy does not substantially increase the probability of bacterial infection in older ED adults and should not be used alone to indicate infection in this population. Fever ≥38°C is associated with increased probability of infection.